Aging, metabolic acidosis and renal failure: Interactive accelerating processes. (March 2019) - Frassetto, L.A.; Sebastian, A.
Abstract: In this article, we hypothesize that eating a low acid (and particularly a low phosphate) diet and/or supplementing the diet with base precursors such as bicarbonate would have a number of helpful effects on aging, by: 1) slowing progressive damage to the kidneys, which would help preserve the kidneys ability to excrete acid and minimize systemic acidosis; 2) avoiding the downregulation of klotho, a membrane and soluble factor associated with aging that decreases with constant high dietary phosphate intake and FGF-23 production; and. 3) potentially improving telomerase activity to help maintain telomere length, another factor associated with longer lifespan. Although the present data is mainly from studies in invertebrate and small animal models, extrapolation of these results, as well as some associated results in human studies, suggests that low acid diets, or neutralization of the low grade metabolic acidosis seen in aging human subjects would possibly allow us to live longer and remain healthier.